Preparation and characterization of light curable hybrid coating: Its potential application for dental restorative material - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (SPRINGER, 2008)
The objective of this study was to synthesize a dual-functional light curable resin by the reaction between acrylated cycloaliphatic epoxy resin and 3-isocyanatopropyltrimethoxysilane and investigate the performance of this oligomer in the preparation of resin-based composite restoratives. FT-IR and (29)Si-NMR were used to characterize the structure of the hybrids. The char yields of the hybrids increased with inorganic content comes from TEOS (tetraethylorthosilicate) and synthesized SiUA oligomers. Gel content of polymeric films was found to be between 95% and 98%. Swelling was found to be between 3.1% and 3.8%. Weight loss of coated human teeth in synthetic saliva solution was found to be among 1% and 2%. There was a systematic increase in the modulus and tensile strength with the increase of inorganic content. On the other hand, elongation at break did not changed. Prepared hybrid coating materials exhibited improvement in tensile properties and hardness, when photo chemically cured.
Keywords: hybrid coating; sol-gel; UV; composite; organic-inorganic; dental; MECHANICAL-PROPERTIES; COMPOSITES; SILANE; RESINS; SALIVA